The Intentional Hospitality: A Christian Paradigm on Religious Moderation in Indonesia - Tobing, Oscard L.; Tamonob, Karmelia (Sekolah Tinggi Teologi Simpson Ungaran, 2025)
This paper critically examines the use of ‘tolerance’ as one of the four indicators in the Indonesian government’s Religious Moderation policy. Since the familiarisation of this idea in 2019, some Christian scholars have widely echoed it, even trying to integrate it with the Bible and Christian values in the practical work of interfaith relations. For us, tolerance is still passive, and this is contrary to Christian teachings or the Bible, which demands that Christians constantly be proactive, including in terms of living together with 'those who are different'. Through this article, we argue that the concept of ‘hospitality’ is a more active and fitting concept for promoting interreligious relations than the indicator appointed by the Indonesian government, ‘tolerance’. We also strongly emphasise that intentional hospitality can be a paradigm of living together in a more biblical and Christian interfaith relationship. In this work, we use a methodology that includes the following components: literature review, theoretical analysis, and critical reflection. By critically reviewing the work of theologians, Amos Yong and Marianne Moyaert, we constructively propose research findings in the five key characteristics of a hospitable interreligious connection: recognition, imagination, transformation, commitment, and intention. These characters, emphatically, demonstrate active involvement and sincere relationships with others, particularly individuals from other faiths.